Understanding Cluster Headache Using Magnetic Resonance Imaging - Ferraro, Stefania; Nigri, Anna; Demichelis, Greta; Pinardi, Chiara; Chiapparini, Luisa; Giani, Luca; Proietti Cecchini, Alberto; Leone, Massimo (Frontiers in Neurology, 2020)
Cluster headache is an excruciating pain syndrome characterized by unilateral head pain attacks, lasting between 15 minutes and 180 minutes, accompanied by marked ipsilateral cranial autonomic symptoms, such as lacrimation and conjunctival injection. Despite important insights provided by neuroimaging studies and deep brain stimulation findings, the pathophysiology of cluster headache and its pathways of chronicization are still elusive. In this mini-review, we will provide an overview of the functional and structural neuroimaging studies in episodic and chronic cluster headache conditions conducted to clarify the underlying pathophysiology.